Impacts of high temperature during early capped brood on pupal development and the size of appendages in adult workers Apis cerana - Xu, Xinjian; Du, Xia; Zhou, Shujing; Zhou, Bingfeng; Lai, Kang; Wang, Qing; Li, Han; Zhu, Chenyu; Xu, Hongzhi; Zhang, Xianlan; Cao, Mingjie; Zhu, Xiangjie (Frontiers in Ecology and Evolution, 2023)
Whether the development of honeybee broods is healthy or not determines the productivity of bee colonies. Pupation is a critical period in the development of holometabolous insects, characterized by the transition from larva to pupa, and its sensitivity to high temperature was investigated in Apis cerana worker bees. Mature larvae (ML), the first and second days of prepupa (PP1 and PP2), and the first day of pupa (P1) were exposed to 40°C for varied durations of time. The mortality, development duration, birth weight, size of the body, and appendages of eclosed Apis cerana worker bees were measured. Results showed that PP1 had the highest mortality, the lowest birth weight, and the longest development duration among the pupation stages. When exposed to 40°C for 12 h and 16 h, more than 28 and 84% of PP1 failed to complete development, respectively. Additionally, high-temperature treatment had a significant effect on the length of the proboscis, the size of the forewing, and the size of the hind leg. These findings suggest that ML and PP1 are crucial checkpoints for wing and appendage (proboscis and legs) development and provide insights into the mechanisms of honeybee brood susceptibility to high-temperature stress in the context of global warming.